2013
DOI: 10.1152/ajpregu.00391.2012
|View full text |Cite
|
Sign up to set email alerts
|

Hindlimb unloading results in increased predisposition to cardiac arrhythmias and alters left ventricular connexin 43 expression

Abstract: Hindlimb unloading (HU) is a well-established animal model of cardiovascular deconditioning. Previous data indicate that HU results in cardiac sympathovagal imbalance. It is well established that cardiac sympathovagal imbalance increases the risk for developing cardiac arrhythmias. The cardiac gap junction protein connexin 43 (Cx43) is predominately expressed in the left ventricle (LV) and ensures efficient cell-to-cell electrical coupling. In the current study we wanted to test the hypothesis that HU would re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
3
12
1
Order By: Relevance
“…The precise interactions of social and environmental stress, depressive behaviors, and altered Cx43 and Cx45 expression are not well defined, however previous findings from a number of studies indicate that appropriate Cx43 communication is important for maintaining cardiac rhythmicity (Beardslee et al 1998; Lerner et al 2000; Bernstein and Morley 2006; Mayama et al 2007), and a reduction in the Cx43/Cx45 ratio may induce a pro-arrhythmic state (Yamada et al 2003; Yamada et al 2004; Betsuyaka et al 2006). The present findings also lend further support to previous data indicating that various forms of psychological and physiological stressors, such as hindlimb unloading (Moffitt et al 2013) and restraint (Unuma et al 2010), disrupt Cx43 expression in the heart. However, whether stress influences cardiac function directly to alter Cx43 and Cx45 expression, or indirectly via neurocardiac communication, is yet to be determined.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The precise interactions of social and environmental stress, depressive behaviors, and altered Cx43 and Cx45 expression are not well defined, however previous findings from a number of studies indicate that appropriate Cx43 communication is important for maintaining cardiac rhythmicity (Beardslee et al 1998; Lerner et al 2000; Bernstein and Morley 2006; Mayama et al 2007), and a reduction in the Cx43/Cx45 ratio may induce a pro-arrhythmic state (Yamada et al 2003; Yamada et al 2004; Betsuyaka et al 2006). The present findings also lend further support to previous data indicating that various forms of psychological and physiological stressors, such as hindlimb unloading (Moffitt et al 2013) and restraint (Unuma et al 2010), disrupt Cx43 expression in the heart. However, whether stress influences cardiac function directly to alter Cx43 and Cx45 expression, or indirectly via neurocardiac communication, is yet to be determined.…”
Section: Discussionsupporting
confidence: 91%
“…Ventricular arrhythmias are more easily provoked in animals deficient in Cx43 (Lerner et al 2000), while significant decreases in the expression of Cx43 have been implicated in the pathogenesis of ventricular arrhythmias following infarction (Takamatsu 2008) and heart failure (Ai and Pogwizd 2005). Interestingly, cardiovascular deconditioning produced through hindlimb unloading increases the incidence of ventricular arrhythmias and is associated with increased expression of Cx43 in rats (Moffitt et al 2013), as does forced restraint (Unuma et al 2010). In addition, changes in Cx43 expression and phosphorylation vary considerably over the time course of development of heart failure in dogs (Akar et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Male Fisher 344-Brown Norway rats (young (10 month old) and old (30 month old)) were assigned to one of two experimental groups: normal or hindlimb-suspension groups. It has been previously shown that 14 days of hindlimb suspension increases the predisposition of rats to get cardiac arrhythmias, while 21 days of hindlimb suspension significantly decreases the turnover rates of cardiac muscle proteins [ 17 , 18 ]. It is possible that ISGylation would be affected in hearts from hindlimb suspended animals since some of the enzymes that promote ISGylation are also involved in ubiquitin conjugation [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Moffitt et al [30] suggests that exposure to microgravity increases the predisposition to cardiac arrhythmias during an acute stressor as a result of altered function of gap junctions, in particular connexin 43 (Cx43). In this study, electrocardiographic data were obtained over a short period of HU using an implantable telemetry device following administration of a sympathetic stressor, isoproterenol, in combination with animal restraint.…”
Section: Discussionmentioning
confidence: 99%